DIRECT FINANCIAL MARKET: ISLAMIC EQUITY MARKET (Bursa Saham dalam Islam) - Timorita Yulianti, Rahmani (Islamic University of Indonesia, 2010)
Islamic capital market is developed in order to accommodate the needs of Muslims in Indonesia who wish to invest in the instrument of capital-market instruments in accordance with Islamic principles. The industrial sector is expected to accommodate the capital market and also involves the participation of Muslim citizens to take active steps directly into the main market actors, namely as local investors in the Indonesian capital market. In an effort to realize this, then it is reasonable provided and developed investment instruments such as shares in the Indonesian capital market in accordance with the principles of Islamic teachings. There are requirements for a stock can be categorized in accordance with the provisions of sharia. Companies issuing shares of Islamic law, a company with business and management that do not conflict with the Sharia, and has a kosher product. The companies will be excluded from the index if it has an Islamic stock exchange for the debt and financial ratios or levels of income from certain interest.